Fluctuations of Current in Polycrystalline Ferroelectric Ceramics - Kartunova, E. I.; Gabrielyan, A. V.; Zhoga, L. V. (Bulletin of the Russian Academy of Sciences. Physics, 2018)
Experimental data on fluctuations of leakage currents over time in samples of polycrystalline ferroelectric ceramics (SBPZT-1, ceramics based on sodium bismuth lead zirconate–titanate) upon the application of a constant electric field are considered. Variations in the type of leakage current dependence on time with an increase in electric field strength on samples with different values of the loss-angle tangent are determined. Exponential decay is accompanied by random jumps, i.e., variations in the values of the leakage current.